2011
DOI: 10.1103/physrevb.83.174416
|View full text |Cite
|
Sign up to set email alerts
|

Cubic interactions and quantum criticality in dimerized antiferromagnets

Abstract: In certain Mott-insulating dimerized antiferromagnets, triplet excitations of the paramagnetic phase display both three-particle and four-particle interactions. When such a magnet undergoes a quantum phase transition into a magnetically ordered state, the three-particle interaction becomes part of the critical theory provided that the lattice ordering wave vector is zero. One microscopic example is the staggered-dimer antiferromagnet on the square lattice, for which deviations from O(3) universality have been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
83
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(88 citation statements)
references
References 50 publications
4
83
1
Order By: Relevance
“…[16,17]) yield (J ′ /J) c ≈ 1.48. In the Shastry-Sutherland material SrCu 2 (BO 3 ) 2 , for which (J ′ /J) ≈ 1.6, the triplon crystalline phases show up as a series of magnetization plateaux at unconventional filling fractions [11,12] that are stabilized by complex manybody interactions among the triplons [9,12,18,19]. Indeed, the magnetization plateaux in SrCu 2 (BO 3 ) 2 at low magnetization are now quite well understood in terms of triplon bound states [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16,17]) yield (J ′ /J) c ≈ 1.48. In the Shastry-Sutherland material SrCu 2 (BO 3 ) 2 , for which (J ′ /J) ≈ 1.6, the triplon crystalline phases show up as a series of magnetization plateaux at unconventional filling fractions [11,12] that are stabilized by complex manybody interactions among the triplons [9,12,18,19]. Indeed, the magnetization plateaux in SrCu 2 (BO 3 ) 2 at low magnetization are now quite well understood in terms of triplon bound states [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…[9]). The first two, each with two sites per unit cell, both have the dimer J ′ bonds parallel (say, along the row direction of the square lattice).…”
Section: Introductionmentioning
confidence: 99%
“…1a) displays a conventional quantum critical point (QCP), the staggered dimer lattice (Fig. 1b) has a QCP with dangerously irrelevant Berry-terms [15].Experimental realizations of systems that could confirm these theoretical ideas are scarce. In this Article, we have studied the magnetic excitations in the mineral malachite, which realizes a variant of the staggered dimer lattice, where half of the interdimer couplings perpendicular to the dimers are removed (see Fig.…”
mentioning
confidence: 99%
“…However, it was recently shown that certain classes of non-frustrated 2D coupled dimers develop non-trivial cubic interactions of purely quantum mechanical origin that lead to simultaneous condensation of the one-triplon and two-triplon excitations at the Γ-point at the critical interdimer coupling strength [15]. These three-particle interactions have been shown to correspond to Berry-phase terms in the O(3) non-linear σ-model [15] and lead to the equivalent of vector boson excitations in the adjacent Néel phase [16]. The geometry of the dimer lattice has been shown to be crucial: While the columnar dimer lattice (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation